Uniqueness of a Solution to the Lavrent’ev Integral Equation in n-Dimensional Space - Kokurin, M. M.; Klyuchev, V. V.; Gavrilova, A. V. (Computational mathematics and mathematical physics, 2024)
We study the multidimensional analogue of the Lavrent’ev integral equation to which an inverse problem of acoustic sounding is reduced. Conditions under which the studied equation has a unique solution are established. Results of numerical experiments concerning the solution of the inverse acoustic problem with variously located sets of sources and detectors are presented.